New species of Cnemaspis (Reptilia: Gekkonidae) from southeastern Thailand - Bauer, Aaron M.; Das, I. (American Society of Ichthyologists and Herpetologists (ASIH), 1998)
A new small species of Cnemaspis, C.chanthaburiensis, is described from Chantaburi & Chon Buri Provinces, Southeastern Thailand. It is the only Cnemaspis occuring in the region and may be distinguished from congeners by its small size (maximum 41 mm svl), smooth ventral and subcaudal scales, 7-9 preanal pores in males, and by hyperphalangy of digits II and V of the manus and digit II of the pes. The hyperphalangeal condition is unique Asian geckos.